PENGARUH PERLAKUAN BIBIT TERHADAP PERKEMBANGAN PENYAKIT LAYU BAKTERI PADA JAHE (ZINGIBER OFFICINALE) - Titik Nur Aeny, Feriansyah, dan Subli Mujim . (Universitas Lampung, 2002)
Effect of seedling treatments on development of bacterial wilt disease of ginger (Zingiber officinale). This experiment was aimed to study the effect of seedling treatment with bactericide on incubation period and disease intensity of bacterial wilt caused by Ralstonia solanacearum on ginger (Zingiber officinale). The experiment was conducted from May to November 2001, and the treatments were set as factorial experiment in completely randomised design. The first factor was the level of bactericide concentrations and the second factor was the length of soaking periods. Each treatment consisted of five plants and was replicated three times. Data were analysed with ANOVA and the means were compared with Duncan test. The results of analysis of variance showed that the interaction of bactericide concentrations with soaking periods was not significantly affected the incubation period and the intensity of bacterial wilt disease of ginger. However, those two factors significantly (P < 0.01) affected the incubation period and the intensity of ginger bacterial wilt disease. Separation of the means by Duncan test indicated that the higher the bactericide concentration, the longer the incubation period. On the other hand, the disease intensity was lowered by the higher concentration. The effect of bactericide concentration 4 g/l was not significantly different from that of 6 g/l. The analysis of variance was also showed that the length of soaking period of ginger seedling in bactericide did not affect the incubation period nor the disease intensity.